The utilisation of the ash disposal system as a salt sink : enhancement and optimisation of chemical interactions - Van den Berg, Jacobus A. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScIng)--University of Stellenbosch, 2004.